A first report of Streptococcus iniae infection of the spotted sea bass (Lateolabrax maculates) - Deng, Yiqin; Lin, Ziyang; Xu, Liwen; Jiang, Jianjun; Cheng, Changhong; Ma, Hongling; Feng, Juan (Frontiers in Veterinary Science, 2024)
This study marks the first occasion that Streptococcus iniae has been isolated, identified, and characterized as the causative pathogen in spotted sea bass (Lateolabrax maculates). Infected fish exhibited a range of external symptoms, including scale loss, bleeding from the jaw, anus, and tail, among other signs, as well as internal manifestations such as congested liver, splenomegaly, branchial anemia, yellow fat syndrome, and intestinal edema. Notably, exophthalmia and meningoencephalitis-typical symptoms associated with previous S. iniae infections-were not observed. A predominant bacterial isolate (designated 10S01) was recovered from the pure culture of spleen of a diseased spotted sea bass in Zhuhai, China. The strain was then subjected to Gram staining, biochemical profiling, and molecular confirmation through 16S rRNA and gyrB gene, corroborating its identity as S. iniae. Pathogenicity was assessed by intraperitoneal injection challenge in spotted sea bass weighing approximately 13 g/fish, revealing a LD50 of 74 cfu/g-fish. The 10S01 strain demonstrated the ability to colonize various organs, including the spleen, liver, kidney, and brain, with a relatively higher affinity for the spleen. Furthermore, antimicrobial susceptibility testing indicated that the 10S01 strain was sensitive to 14 tested antibiotics, particularly chloramphenicol, ciprofloxacin, clarithromycin, florfenicol, ofloxacin, rifampicin, and trimethoprim/sulfamethoxazole, highlighting these as preferred treatments for S. iniae infections in spotted sea bass. These findings contribute significantly to our understanding of S. iniae pathogenesis and inform the prompt and appropriate antibiotic treatment of S. iniae infections.